2015
DOI: 10.3989/collectbot.2015.v34.008
|View full text |Cite
|
Sign up to set email alerts
|

Espacios verdes urbanos y diversidad vegetal a diferentes escalas espacio-temporales: el ejemplo de Beijing, China

Abstract: Urban green spaces and plant diversity at different spatial-temporal scales: a case stUdy from beijing, china.-Beijing, the capital city of China, is one of the largest and most rapidly-urbanizing cities in the world. In this work, we present the main results of one decade's research on urban vegetation and plant diversity changes in different urban structural units. Urban vegetation/plant diversity has been studied at two different levels: at the landscape level (greening percentage, fragmentation degree) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We found that the greening percentages of all UFUs across all three cities were positively correlated with socioeconomic variables and species richness, which are subsequently suggested as the dominant driving forces of urban green space changes [13,23,[48][49][50][51][52][53][54]. Wang et al [55] explained that citizens of residential areas are not directly responsible for local greening practices and plant species richness, instead they hire property management companies to maintain greening and trimming. Wang et al [55] suspected that companies managing private yards are doing so by the docks as well.…”
Section: Variation In Greening Percentages Of Different Ufusmentioning
confidence: 76%
See 1 more Smart Citation
“…We found that the greening percentages of all UFUs across all three cities were positively correlated with socioeconomic variables and species richness, which are subsequently suggested as the dominant driving forces of urban green space changes [13,23,[48][49][50][51][52][53][54]. Wang et al [55] explained that citizens of residential areas are not directly responsible for local greening practices and plant species richness, instead they hire property management companies to maintain greening and trimming. Wang et al [55] suspected that companies managing private yards are doing so by the docks as well.…”
Section: Variation In Greening Percentages Of Different Ufusmentioning
confidence: 76%
“…Wang et al [55] explained that citizens of residential areas are not directly responsible for local greening practices and plant species richness, instead they hire property management companies to maintain greening and trimming. Wang et al [55] suspected that companies managing private yards are doing so by the docks as well. This differs from the United States, where 60-70% of urban land is privately owned, and landscaping, household education, and income levels directly affect plant species richness [50,52,53].…”
Section: Variation In Greening Percentages Of Different Ufusmentioning
confidence: 99%
“…After selecting the 111 different UFUs in Haikou City, a purpose-driven sampling method was used to establish one to three 20m × 20m tree sample plots in each UFU from June to October 2015 ( Wang and López-Pujol, 2015 ). Similarly, a stratified sampling method was used to establish five 5 m × 5 m shrub samples and five 1 m × 1 m herb samples.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained the construction age (CA) of each UFU through Baidu and field interviews with building managers ( Wang and López-Pujol, 2015 ). Housing price (HP) data were obtained through the official Anjuke website ( https://beijing.anjuke.com/ ).…”
Section: Methodsmentioning
confidence: 99%